Optimisation and Problems of the Channel Area Formed by Two Ion Implantations in NMOS Structures - Kašauskas, V.; Anilionis, R. (Elektronika ir Elektrotechnika, 2010)
NMOS nano-structure channel structure depends on a number of technological processes. It is important to find and evaluate depend of technological operationts (TO) parameters to NMOP structures and output caharacteristics. The number of TOs in fabrication process is big, therefore it is difficult to evaluate and carry out optimization of all factors xi (TO parameters). Wherefore proposed optimization algorithm of 4 factors xi (energy and dose of to ion implantations parameters) by set output parameter value y (L) with the given allowable tolerance ε. This model is applicable for NMOS structures with designed 90 nm chanel.